Ibudilast may improve attention during early abstinence from methamphetamine. (1st September 2017) - Birath, J. Brandon; Briones, Marisa; Amaya, Stephanie; Shoptaw, Steven; Swanson, Aimee-Noelle; Tsuang, John; Furst, Benjamin; Heinzerling, Keith; Obermeit, Lisa; Maes, Lauryn; McKay, Charles; Wright, Matthew J.
Highlights: Ibudilast is proposed as a treatment for inattention in methamphetamine dependence. Participants receiving ibudilast show reduced inattention in early abstinence. Ibudilast shows promise as adjunctive therapy during methamphetamine withdrawal. Abstract: Background: Inattention is a deficit related to instilling abstinence from methamphetamine (MA) dependence. This study aimed to determine whether ibudilast (IB; 50 mg bid) improves attentional abilities compared to placebo during early abstinence from MA dependence. Methods: Attention was assessed in 11 MA-dependent non-treatment seeking participants in a phase IB safety-interaction trial. The Conners' Continuous Performance Test-II (CPT-II), a measure of sustained attention and response inhibition, was administered at baseline and on day 22, 48 h post a MA challenge under placebo (P; n = 6) or IB 50 mg bid (n = 5). Group differences were compared using Mann-Whitney U Tests. Groups were similar at baseline in premorbid intellectual functioning, attention deficit hyperactivity symptom scores, impulsivity ratings, and education level, but differed in age. Demographically corrected T-scores for CPT-II performances were utilized. Results: Although no group differences in sustained attention existed at baseline, at follow-up, the IB group (Mdn = 44.4) showed reduced variability in response times compared with the P group (Mdn = 69.9), U = 0.00, z = −2.74, p =.006, r = .83. The IB group (Mdn = 45.8) also gave fewer perseverative responses than the P group (Mdn = 67.0), U = 2.00, z = −2.50, p = .01, r = .75. No other significant differences were observed. Conclusions: Findings suggest that IB may have a protective effect on sustained attention during early abstinence from MA dependence. This may guide thinking about mechanism of action should IB demonstrate efficacy as a treatment for MA dependence.